Demonstração de valor adicionado e balanço social: contribuição de evidenciação para as empresas na região de Uberaba - Carvalho, Fernando Rodrigues de (2007)
The aim of this paper is to show the relevance and contribution of the social data pertaining to the Social Report and mainly to the Added Value Statement. It is credited that its disclosure may help evaluate its effects upon the social environment as well as the remuneration attributed to several production factors. The wealth of management and financial data available is evidenced through the magnitude of the company of choice- Black & Decker do Brasil, a high income multi-national firm with limited responsibility and no obligation to publish its accounting reports. However, the 3.741/2000 bill which states that it is mandatory to make the accounting, financial , economic and social, led us to verify the applicability of such publications and the indexes of analysis commonly used. A bibliographic study, the Internet and a questionnaire given to one of the directors of the company were used to evaluate the applicability of such management ools. The diversity of material found in the Added Value Statement and the Social Report, which was used in the analyses, figures and conclusions, outstands the need of commitment of the productive sector in publishing their reports not only to their own clients but also to aware the general public of the responsibility of such companies in the economic context. Also, they would assure their reliability together with their politically correct role regarding the other stakeholders